The key problems of economic reconstruction and development in Nigeria - Letiche, John M.; Nigerian Institute of International Affairs (Lagos : Nigerian Institute of International Affairs, 1969)
This is first publication of the Nigerian Institute of International Affairs in its Lecture Series, by Professor J. M. Letiche of the University of California at Berkeley. Professor Letiche expresses surprise that the Nigerian economy has remained so healthy under the impact of civil war but stresses that the economic future of the country will depend on its educated manpower.
"Revised for publication in April 1969."
lje 2/10/18
Loans
Keywords: Economic development; Economic policy; Economic history; Economic conditions; Nigeria